Recent Writing on Health Care History in Canada - Twohig, Peter (Scientia Canadensis, 2002)
AbstractThese are halcyon days for health care history in Canada. One routinely sees articles pertaining to health in leading Canadian and international history journals. The Canadian Bulletin of Medical History is a vibrant and important vehicle and there are a growing number of monographs. This essay reviews several of the maturing content areas that now characterize the writing of health history in Canada, including hospital history, nursing history, the history of mental health, and health and medicine in aboriginal settings. This essay seeks to highlight the accomplishments of the field, while reviewing some of the gaps.